2012
DOI: 10.3758/s13415-012-0094-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal responses to sources of dual-task interference

Abstract: There is a response selection bottleneck that is responsible for dual-task interference. How the response selection bottleneck operates was addressed in three dual-task experiments. The overlap between two tasks (as indexed by the stimulus onset asynchrony [SOA]) was systematically manipulated, and both reaction time and electrodermal activity were measured. In addition, each experiment also manipulated some aspect of the difficulty of either task. Both increasing task overlap by reducing SOA and increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…SCRs to auditory attention predicted reaction time slowing in a concurrent visual response task, indicating that enhanced SCR and attention to a primary target depleted cognitive resources that could be allocated elsewhere [100]. Task difficulty appears to affect physiological arousal, as SCRs increase with higher cognitive load during the N-back task [101,102], sentence repetition task [103], and dual-task interference [104]. Further, shifting attention toward reinforcing stimuli may enhance arousal [105] as well as activate preparatory motor mechanisms [106], in support of a link between attention, enhanced arousal and behavioral performance.…”
Section: Discussionmentioning
confidence: 99%
“…SCRs to auditory attention predicted reaction time slowing in a concurrent visual response task, indicating that enhanced SCR and attention to a primary target depleted cognitive resources that could be allocated elsewhere [100]. Task difficulty appears to affect physiological arousal, as SCRs increase with higher cognitive load during the N-back task [101,102], sentence repetition task [103], and dual-task interference [104]. Further, shifting attention toward reinforcing stimuli may enhance arousal [105] as well as activate preparatory motor mechanisms [106], in support of a link between attention, enhanced arousal and behavioral performance.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that most of the studies investigating emotional control used explicit emotion regulation strategies. These strategies could be cognitively effortful, and it has been shown that increasing task difficulty, thus engaging more cognitive resources, results in increased EDA activity (Hartley, Maquestiaux, Brooks, Festini, & Frazier, 2012). Conversely, modulation of emotional response toward fiction could be more implicit and automatic.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the central attentional bottleneck, this theory has been termed the active-scheduling account. However, other authors suggested that EF are not needed to coordinate the processing of the tasks at the stage of the bottleneck ( Jiang et al, 2004 ; Lehle et al, 2009 ; Hartley et al, 2012 ). Instead, the processing would work purely on a first-come first-served basis, a theory which has been called the passive queuing account.…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding that such central arrival times can determine or affect processing order does not rule out that under different task conditions the processing order may be determined by hierarchically higher control processes ( De Jong, 1995 ; Luria and Meiran, 2003 ; Leonhard et al, 2011 ; Strobach et al, 2021a ) and that EFs are required for other aspects besides task-order coordination, such as inhibition of the second task to not interfere with the first task or switching the bottleneck between tasks. Further evidence for the passive queuing account comes from the observation that increasing overlap of the tasks (i.e., shorter SOA), which can be postulated to increase the demands on EFs, does not result in the expected electrodermal responses ( Hartley et al, 2012 ). Finally, in an fMRI study Jiang et al (2004) were unable to observe any brain activation linked to dual-task processing, again supporting the passive queuing approach.…”
Section: Introductionmentioning
confidence: 99%